Epidemiologic analysis of prevalence of the hyperhidrosis - Fernanda Alvarenga Estevan; Marina Borri Wolosker; Nelson Wolosker; Pedro Puech-Leão (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: The present paper aims to study the prevalence of the various manifestations of hyperhidrosis in patients who sought treatment in a specialized ambulatory in the state of São Paulo. Objectives: Opposite to previous studies, this paper studies the different combinations of sweating sites, not being restricted to the main complaint site of the patients, but taking into consideration secondary complaints patients may present. Methods: This was a retrospective approach of a database containing more than 1200 patients in which were mapped: combination of sweating sites, age of onset, age spectrum, mean age, body mass index and gender of patients. Patients were categorized into four groups based on their main sweating site - palmar, plantar, axillary and facial. Results: We concluded that hyperhidrosis appears frequently in more than one site, being the main complaint that affects the most patients palmar hyperhidrosis, which appears early in the patients during adolescence. When there are two sites of sweating, the most frequent combination is palmar + plantar, and when there are three sites of sweating the most frequent combinations are palmar + plantar + axillary and axillary + palmar + plantar. Study limitations: This research has casuistics limited to a single care service for patients with hyperhidrosis. Conclusion: It is necessary to keep in mind that the disease manifests itself mainly in more than one location, with different intensities in each of the patients, generating a significant impairment of their quality of life.